Pengaruh Current Ratio, Suku Bunga dan Kondisi Finansial Distress terhadap Return Saham pada Perusahaan Manufaktur Subsektor Pulp dan Paper yang Terdaftar di Bursa Efek Indonesia Periode 2015-2024 - Aryati Aryati; Kenedi Kenedi; Furtasan Ali Yusuf (Jurnal Ilmiah Manajemen dan Kewirausahaan, 2025)
Stock returns serve as a key indicator for maximizing profits and minimizing investment risks. This study aims to examine the effect of Current Ratio, Interest Rate, and Financial Distress on Stock Returns in both the short term and long term for manufacturing companies in the pulp and paper sub-sector listed on the Indonesia Stock Exchange during the 2015–2024 period. The research employs a quantitative approach with a sample of 7 companies selected through purposive sampling. Data were analyzed using the Panel Autoregressive Distributed Lag (ARDL) method with the assistance of Eviews 12 software. The results show that in the short term, Current Ratio and Interest Rate do not significantly affect Stock Returns, while Financial Distress has a significant effect. In the long term, Current Ratio, Interest Rate, and Financial Distress all have a significant effect on Stock Returns. These findings imply that investors should carefully consider both company fundamentals and external macroeconomic factors when making investment decisions, particularly for long-term investments.